Comparative study on using chemical and natural admixtures (grape and mulberry extracts) for concrete. (December 2021) - Mahmood, Hersh F.; Dabbagh, Hooshang; Mohammed, Azad A.
Abstract: There is a general belief that admixture can improve some important properties of concrete, and different kinds of admixtures are in use worldwide. In the current investigation, a comparative experimental study has been performed on using grape and mulberry extracts as a natural admixture and chemical admixture for concrete. Increasing of workability and reduction in water absorption were observed due to the addition of natural admixtures to concrete. There was an enhancement of concrete compressive strength tested at 3, 7, and 28 days and the 28 days modulus of elasticity as a result of using different admixtures, but reduction of splitting tensile strength was observed. In general, using the two natural admixtures has a beneficial effect to improve both fresh and hardened properties of concrete and they have a superiority on the chemical admixture with regard the cost and producing environmental-friendly construction material.